International Monetary Fund Annual Report 2002 : Making the Global Economy Work for All. (Annual Report of the Executive Board; Annual Report of the Executive Board, 2002)
This 2002 Annual Report describes world economic and financial developments in FY2002. During FY2002, the IMF faced important new challenges in an unusually unsettled world environment. After a period of strong expansion, the global economy experienced a widespread slowdown during the 2001 calendar year. By early 2002, however, thanks in large part to actions taken by key central banks to lower interest rates, there were encouraging signs that growth was recovering, although serious concerns remained in a number of countries.